Application of empirical models to bay shaped beaches in Portugal - Oliveira, F. S. B. F. (2010)
Three models were applied to analyse the planform of bay-shaped Portuguese beaches. They are based on empirical mathematical functions: the logarithmic spiral bay equation, the hyperbolic tangent bay equation, and the parabolic bay equation. These models were applied to analyse the fitting to the beach planform of 42 beaches on the Portuguese Atlantic coast which was calculated through the validation against the waterline extracted from rectified aerial photographs. The logarithmic spiral model fits well the curved zone of the beaches, in particular small beaches with two headlands. Despite the good fitting of the hyperbolic tangent model for one headland beach, its process of approximation to the solution was less intuitive than the processes of the other two models, therefore its application was more exhaustive. A comparative analysis between the logarithmic spiral model and the hyperbolic tangent model revealed the best fit of the first. The application of the parabolic model allowed to conclude that despite the majority of the beaches analysed being in dynamic equilibrium condition due to the high energy wave regime of the Portuguese Atlantic coast, their planform was very close to the planform in static equilibrium condition due to the high dynamics of the coastal environment